PENGARUH BIBLIOTERAPI SUFISTIK DALAM MENINGKATKAN REGULASI DIRI SANTRI - Halimatus Sa’diyah; Nuzulul Khair; Zamzami Sabiq (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2022)
Self-regulation plays an important role in the process of individual growth and development, especially in the adolescent and early adult age ranges. This study aims to determine the effect of sufistic bibliotherapy on the self-regulation of students at Annuqayah Latee 1 Islamic Boarding School.The research method uses an experimental design with a pretest-posttest control group design. The population was mostly female students at the Annuqayah LateeI Islamic Boarding School. The research sample consisted of 20 female students, each group consisting of 10 female students. Respondents were chosen randomly to equalize the experimental group and the control group. The scale used is a self-regulation scale developed by researchers. The treatment for the experimental group was reading stories related to Sufi figures, while the control group was not given treatment.This study concluded that sufistic bibliotherapy is effective for increasing self-regulation inlearning, as shown by the results of the paired sample t-test, which has a significance value of 0.001 (0.0010.05). Female students who received treatment obtained a higher average increase in self-regulation (62) than before receiving treatment (56.4).There was a posttest difference between the self-regulation conditions of the experimental group and the control group after the experimental group was given treatment, as indicated by the results of the independent sample t-test, which had a significancevalue of 0.002 (0.0020.05). Based on these results, it can be concluded that sufistic bibliotherapy is effective for increasing the self-regulation of students at Annuqayah Latee 1 Islamic Boarding School.